Uji viabilitas dan pertumbuhan benih kedelai (Glycine max) dengan perlakuan invigorasi menggunakan ekstrak bawang merah - Indah Lestari; Karno Karno; Sutarno Sutarno (Department of Agriculture, Animal and Agricultural Sciences, Diponegoro University, Semara, 2020)
ABSTRACT The purpose of this research was to examine the effect of the interaction between the different dosages of shallot extract and immersion time on the viability and growth of Kaba soybean seed varieties that have been stored since 2013. This research used a completely randomized factorial design. The first factor was the dosages of onion extract (D0 = 0% D1 = 40% D2 = 60% and D3 = 100%). The second factor is the immersion time (P1 = 3 hours P2 = 6 hours and P3 = 9 hours). The parameters during seed germination were seed germination, vigor index, maximum growth potential, seed growth speed and electrical conductivity. Growth stage (vegetative) parameters consist of plant height and number of leaves. The data were analyzed by variance analysis and continued analyzed by Duncan's Multiple Range Test. The results showed that there is an interaction between the different dosages of shallot extract and immersion time. Dosages 40%, 60%, 100% increased seed germination, vigor index, maximum growth potential, growth rate, plant height and the number of leaves compare to control (0%). There was no influence of different immersion time on increased seed germination, vigor index, maximum growth potential, growth rate, plant height and the number of leaves. Keywords : Invigoration, Seed Viability, Onion Extract, Glycine max ABSTRAK Penelitian ini bertujuan untuk mengkaji pengaruh interaksi antara perbedaan dosis ekstrak bawang merah dan lama perendaman terhadap viabilitas dan pertumbuhan benih kedelai varietas Kaba yang telah disimpan sejak 2013. Penelitian ini menggunakan Rancangan Acak Lengkap (RAL) pola faktorial 4x3. Faktor pertama adalah konsentrasi ekstrak bawang merah (K0 = 0% K1 = 40% K2 = 60% dan K3 = 100%). Faktor kedua adalah lama perendaman masing-masing bahan (P1 = 3 jam P2 = 6 jam dan P3 = 9 jam). Variabel yang diamati pada masa perkecambahan benih antara lain daya kecambah benih, indeks vigor, potensi tumbuh maksimum, kecepatan tumbuh benih dan daya hantar listrik. Variabel pada tahap pertumbuhan (vegetatif) terdiri dari tinggi tanaman dan jumlah daun. Data yang diperoleh dianalisis dengan anova dan dilanjutkan dengan uji Duncan. Hasil penelitian menunjukkan terjadi interaksi pemberian dosis dan lama perendaman pada fase perkecambahan. Dosis 40%, 60%, dan 100% dapat meningkatkan daya berkecambah, indeks vigor, potensi tumbuh maksimum, kecepatan tumbuh benih, tinggi tanaman dan jumlah daun dibandingkan dengan kontrol (0%). Lama perendaman tidak berpengaruh terhadap daya berkecambah, indeks vigor, potensi tumbuh maksimum, kecepatan tumbuh benih, tinggi tanaman dan jumlah daun. Kata kunci: Invigorasi, Viabilitas Benih, Ekstrak Bawang Merah, Kedelai